Enhancing Community Pharmacists’ Professional Competencies and Sun-Safe Behaviors Through the FarmaSoludable Educational Program - Guillermo J. Pozuelo-Sánchez; Magdalena de Troya-Martín; Francisco Rivas Ruiz; Alba Rodriguez-Martinez; Andras Subert; Maria Alvarez de Sotomayor (Journal of Cancer Education, 2026)
This study examined the impact of a structured educational intervention on professional competencies in individualized photoprotection counselling and on personal sun-safe behaviors. A quasi-experimental pre–post study was conducted among community pharmacists in Seville, Spain, in 2024. The intervention consisted of a blended educational program comprising an online training course delivered by a multidisciplinary faculty and a one-day practical session. Professional counselling practices were assessed using the Counselling Habits in Individualized Photoprotection questionnaire, while personal habits, attitudes, and knowledge related to photoprotection were evaluated using the Habits, Attitudes, and Knowledge in Photoprotection questionnaire. Data were collected at baseline and after completion of the intervention, and analyses included descriptive and comparative pre–post statistics, with statistical significance set at p < 0.05. A total of 116 pharmacists completed the baseline professional assessment and 80 the post-intervention, while 125 and 85 pharmacists completed the personal behavior questionnaire, respectively. Professional competencies improved significantly, including identification of skin cancer risk factors (45.2% to 72.2%), promotion of skin self-examination (31.6% to 65.8%), and adaptation of counselling to occupational sun exposure ( p < 0.001). Knowledge scores increased from 6.03 to 7.07 ( p < 0.001). Personal sun-safe behaviors also improved, including sunscreen use, regular reapplication, and reduced sunburn frequency. Knowledge of early skin cancer detection criteria increased markedly (ABCDE rule: 61.5% to 100%; ugly duckling sign: 27.9% to 98.8%; p < 0.001). The FarmaSoludable educational program improved professional competencies and personal preventive behaviors, supporting pharmacists’ roles as behavioral role models and educators for community knowledge transfer.